2016
DOI: 10.1158/2159-8290.cd-15-0843
|View full text |Cite
|
Sign up to set email alerts
|

IL35-Producing B Cells Promote the Development of Pancreatic Neoplasia

Abstract: A salient feature of pancreatic ductal adenocarcinoma (PDA) is an abundant fibroinflammatory response characterized by the recruitment of immune and mesenchymal cells and the consequent establishment of a pro-tumorigenic microenvironment. Here we report the prominent presence of B cells in human pancreatic intraepithelial neoplasia (PanIN) and PDA lesions as well as in oncogenic K-Ras-driven pancreatic neoplasms in the mouse. The growth of orthotopic pancreatic neoplasms harboring oncogenic K-Ras was significa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
231
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 294 publications
(267 citation statements)
references
References 32 publications
11
231
2
2
Order By: Relevance
“…Interestingly, recent work in Kras-driven PDAC GEMMs has shown that depletion of tumor stroma or targeting Cxcl12 from tumor-associated fibroblasts exhibits a synergistic effect with immune checkpoint therapies (Feig et al 2013;Ozdemir et al 2014), suggesting that conditioning of the PDAC stroma might be a prerequisite for attaining therapeutic responses to immunotherapies. In addition, stroma-derived Cxcl13 has been shown to induce the infiltration of B-cell subpopulations and promote tumor growth, likely through programming TAMs toward an M2 phenotype (Gunderson et al 2015;Lee et al 2015;Pylayeva-Gupta et al 2015). Importantly, targeting Bruton's tyrosine kinase (BTK), a key kinase for B-cell and TAM function, suppresses tumor progression in an orthotopic PDAC mouse model through the induction of TILs (Gunderson et al 2015).…”
Section: Prospect Of Pdac Immunotherapymentioning
confidence: 99%
“…Interestingly, recent work in Kras-driven PDAC GEMMs has shown that depletion of tumor stroma or targeting Cxcl12 from tumor-associated fibroblasts exhibits a synergistic effect with immune checkpoint therapies (Feig et al 2013;Ozdemir et al 2014), suggesting that conditioning of the PDAC stroma might be a prerequisite for attaining therapeutic responses to immunotherapies. In addition, stroma-derived Cxcl13 has been shown to induce the infiltration of B-cell subpopulations and promote tumor growth, likely through programming TAMs toward an M2 phenotype (Gunderson et al 2015;Lee et al 2015;Pylayeva-Gupta et al 2015). Importantly, targeting Bruton's tyrosine kinase (BTK), a key kinase for B-cell and TAM function, suppresses tumor progression in an orthotopic PDAC mouse model through the induction of TILs (Gunderson et al 2015).…”
Section: Prospect Of Pdac Immunotherapymentioning
confidence: 99%
“…Several recent investigations in mouse cancer models have revealed the existence of protumorigenic regulatory B cells (Breg; refs. [16][17][18]. Here, we identifi ed a novel protumorigenic PD-1 hi B-cell subset in human hepatocellular carcinoma (HCC).…”
Section: Introductionmentioning
confidence: 99%
“…30 Genetic models of oncogenesis have been used extensively to document immune-mediated tumor promotion in solid cancers. 25,30,[40][41][42] However, evidence of immunosurveillance and immunoediting in genetic models of "solid," non-lymphoid, oncogenesis have been sparse and have yielded conflicting results. 34,43 For example, in the p53 ¡/C model of oncogenesis, knockout of Ifngr1 accelerated tumor onset and the spectrum of tumors of non-lymphoid origins.…”
Section: Discussionmentioning
confidence: 99%